MEMPOSISIKAN ANAK YANG LAHIR DILUAR NIKAH SECARA HUKUM ISLAM - Henderi Kusmidi (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Humans are the only creatures who  are entrusted with managing this earth  as His caliph.  Therefore the existence of human beings  should  be sustained. In this regard  humans are given the ability to have sexual intercourse for the sake  of the process of regeneration of the human species in a sustainable manner. Or with other terms of sexuality is a universal process media in the context  of the preservation of creation. Not only that, sexual  pleasure in Islam is considered as being  privileged.  So life with legitimate partner (married) are  more honored than the single life. Thus aqad marriage essentially as a means true, dignity and respect for every human being in order to channel their biological desires. This is where Islam prohibits any form of sexual  relations that are not done  correctly and with dignity as adultery, sodomy, and so on. Because in addition  to violating the rules of religion, is also incompatible with the position of the human beings with dignity and respect. Even adultery by Divine religions is considered as one of the biggest and dirtiest forms of crimes  against humanity, while the base of the onset  of the destruction of the joints civic and adultery are also categorized as one of the major sins